Keanekaragaman Jenis Burung di Kawasan Wisata Pantai Sawarna Kecamatan Bayah Kabupaten Lebak Provinsi Banten - Fajari, Miftah Falahudin; Qohhar, Jamal Abdul; Novita Rahmawati; Monica Ramadyan Affandi; Aida Zuleika Khurotul Aeni; Kurnia, Insan (Universitas Bengkulu, 2024)
Birds are ecosystem components that can adapt to human-dominated landscapes. Therefore, they can be found in various man-made landscapes. The Sawarna Beach Tourism Area (SBTA) is a combination of natural and rural landscapes and is developing as a tourist destination. This research aims to analyze the diversity of birds in SBTA. The study was conducted in June 2023 in three types of habitats (beach, farm, and paddy fields). Bird data was taken using the point count method, while habitat data was described according to the main components are vegetation and substrate. Bird data was analyzed quantitatively and qualitatively with (1) species Diversity Index (H'), (2) species Evenness Index (E), and (3) community Similarity Index (IS). There were 32 birds species found from eight orders and 18 families. Of all the species, nine are protected species under Indonesian law, and one species is listed in Appendix II on the CITES-listed animals. The birds found are seabirds e.g. White tern (Gygis alba); shorebirds e.g. Little ringed plover (Charadrius dubius); water birds e.g. Great egret (Ardea alba); as well as terrestrial birds e.g. Streaked weaver (Ploceus manyar) and Javan-green magpie (Cissa thalassina). Variations in bird groups result from differences in habitats. The H' value is 2.39, which is classified as a medium category, and the E value of 0.68 is also classified as a medium category. The IS value indicates that the farm and paddy field habitats have a greater IS value than the beach habitat.